Incremental detection of pulmonary tuberculosis among presumptive patients by GeneXpert MTB/RIF® over fluorescent microscopy in Mwanza, Tanzania: an operational study - Jeremiah Seni; Benson R. Kidenya; Mercy Anga; Anthony Kapesa; John R. Meda; Richard Mutakyawa; Zahra H. Mkomwa; Fidelis Marcel; John M. Changalucha; Stephen E. Mshana (Healthcare in Low-resource Settings, 2015)
Laboratory confirmation among presumptive tuberculosis (PTB) patients is pivotal in ensuring prompt management. Limited information exists in Tanzania regarding the performance of GeneXpert MTB/RIF® in comparison with conventional methods. An operational study was conducted involving 806 PTB patients at Sekou Toure Hospital in Mwanza, Tanzania from June to November 2013. Patients’ information was obtained and their respective sputum samples analyzed by lightemitting diode fluorescent microscopy (LED FM) and GeneXpert MTB/RIF®. The mean age of study participants was 39.6±16.0 years, with males accounting for 50.5%. The majority of patients (97.5%) were new cases. The proportions of PTB patients confirmed by LED FM and GeneXpert MTB/RIF® were 14.1% (114/806) and 23.7% (191/806) respectively, resulting into a 9.6% incremental detection rate by GeneXpert MTB/RIF® over LED FM. The detection rate among HIV positive individuals was also higher [23.6% (63/267) vs 14.2% (38/267), respectively], with an incremental detection of 9.4%. The incremental detection of PTB by GeneXpert MTB/RIF® over LED FM calls for expansion of its use to increase detection of smear negative PTB among people living with HIV.